Managmante Of Compilation and Explanation of The Strategic Sports Plan of The Social Security Organization of Iran - GAVARSHKI, MOJGAN NADERZADEH; PEYMANIZAD, DR. HOSSEIN; DUVIN, DR. HASSAN FAHIM (The journal of contemporary issues in business and government, 2021)
Today, most organizations need to develop a strategic plan to increase capabilities, long-term growth and survival and reduce the risk of their operations. The purpose of this study was to develop and explain the strategic sports plan of the Social Security Organization of Iran. The method of the present study was applied in terms of nature and purpose and in terms of descriptive-analytical analysis, which was done in the field. The statistical population in the qualitative part included the elites of strategic planning in sports and in the quantitative part included all the employees of the Social Security Organization. The sampling method was qualitative in part and purposeful in quantitative part. Using semi-organized interviews, questions were asked to identify strengths, weaknesses, opportunities and threats. To statistically describe the sample, determine the strengths, weaknesses, opportunities and threats, as well as the current and desired status of descriptive statistics, from the comparison test of the average size of an attribute about the community, the comparison test to evaluate the status of each questionnaire to determine the points Weaknesses, strengths, opportunities and threats and Friedman ranking test was used to rank the most important weaknesses, strengths, opportunities and sports threats of the Social Security Organization. The results showed that the strategic position of sports in the Social Security Organization is such that it has many strengths in this field, but environmental threats have a greater impact on sports in the Social Security Organization and most of the selected strategies are ST. However, Social Security sports can also use WT, SO and WO strategies depending on the circumstances.